2005
DOI: 10.1002/ijc.21257
|View full text |Cite
|
Sign up to set email alerts
|

FXYD3 is overexpressed in pancreatic ductal adenocarcinoma and influences pancreatic cancer cell growth

Abstract: The expression and localization of FXYD domain containing ion transport regulator 3 (FXYD3), a transmembrane protein that acts as a chloride channel or chloride channel regulator, was analyzed in pancreatic tissues derived from donors and patients suffering from chronic pancreatitis (CP) or pancreatic ductal adenocarcinoma (PDAC) as well as in pancreatic cancer cells using QRT-PCR, laser-capture microdissection and microarray analysis, in situ hybridization and immunohistochemistry. FXYD3 antisense expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 24 publications
8
65
1
Order By: Relevance
“…Keratin has been confirmed to be associated with colorectal carcinoma. Fibulin-like extracellular matrix protein 1 (fibulin1) and Fxyd3 protein have been confirmed as overexpressed in gastric adenocarcinoma, colorectal cancer, pancreatic cancer, and other tissue cancers [20,21]. A number of apoptosis-and cancer-related genes showed increased expressions in the liver of rats, indicating that the Dendrobium mixture helped to maintain normal cell differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin has been confirmed to be associated with colorectal carcinoma. Fibulin-like extracellular matrix protein 1 (fibulin1) and Fxyd3 protein have been confirmed as overexpressed in gastric adenocarcinoma, colorectal cancer, pancreatic cancer, and other tissue cancers [20,21]. A number of apoptosis-and cancer-related genes showed increased expressions in the liver of rats, indicating that the Dendrobium mixture helped to maintain normal cell differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that the peaks in the PISEMA spectrum will have to be fitted with Pisa wheels of different tilts, in agreement with the solution NMR studies in micelles, showing that helices 1 and 2 have different orientations. According to the data in micelles, the peaks in the spectrum of 15 N-Leu labeled CHIF should account for Leu 17 and 19 in helix 1 preceding the transmembrane helix (helix 2), and Leu 22,27,28,35,37 in the transmembrane helix.…”
Section: 34mentioning
confidence: 99%
“…FXYD2 (gamma) and FXYD4 (CHIF; channel-inducing factor; corticosteroid hormone induced factor), are each expressed in distinct, specialized segments of the kidney, with unique expression patterns that help explain the physiological differences in Na,K-ATPase activity among the nephron segments [21][22][23][24][25]. FXYD3 (Mat8; mammary tumor protein 8 kDa) is expressed in cancers and plays a role in tumor progression [26,27]. Despite their relatively small sizes ranging from about 60-160 amino acids, all FXYD proteins are encoded by genes with six to nine small exons, and NMR has shown that the protein structures reflect the structures of their corresponding genes, suggesting that they were assembled from modules through exon shuffling [28].…”
Section: Introductionmentioning
confidence: 99%
“…FXYD-3 is a trans-membrane protein normally present in body tissues but overexpressed in several cancers. Increased expression in early tumour differentiation and tumour proliferation has indicated that it could possibly be used as a tumour marker (19,(71)(72)(73)(74)(75). There are also indications that FXYD-3 may be involved in tumour resistance to 5-FU chemotherapy (76).…”
Section: Study Imentioning
confidence: 99%